Essential oil composition from fresh and dried leaves of C. tamala - Chowdhury, JU; Shaha, GC; Begum, F; Bhuiyan, MNH; Rahim, M (Bangladesh Journal of Scientific and Industrial Research, 2013)
The essential oil of Cinnamomum tamala Nees grown at laboratory campus of BCSIR, Dhaka was obtained from its fresh and dried leaves by hydrodistillation. The oils were analyzed by GC-MS. The major components in the fresh leaf oil were eugenol (75.28%) followed by spathulenol (10.06%), eugenyl acetate (9.82%) and in the dried leaf oil were eugenol (68.02%), spathulenol (12.73%), methyl eugenol(6.42%), ?-humulene (4.35%) & caryophyllene (3.58%). Bangladesh J. Sci. Ind. Res. 48(2), 151-154, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15747